Replicative Homeostasis: A fundamental mechanism mediating selective viral replication and escape mutation - Sallie Richard (Virology Journal, 2005)
Abstract Hepatitis C (HCV), hepatitis B (HBV), the human immunodeficiency viruses (HIV), and other viruses that replicate via RNA intermediaries, cause an enormous burden of disease and premature death worldwide. These viruses circulate within infected hosts as vast populations of closely related, but genetically diverse, molecules known as "quasispecies". The mechanism(s) by which this extreme genetic and antigenic diversity is stably maintained are unclear, but are fundamental to understanding viral persistence and pathobiology. The persistence of HCV, an RNA virus, is especially problematic and HCV stability, maintained despite rapid genomic mutation, is highly paradoxical. This paper presents the hypothesis, and evidence, that viruses capable of persistent infection autoregulate replication and the likely mechanism mediating autoregulation – Replicative Homeostasis – is described. Replicative homeostasis causes formation of stable, but highly reactive, equilibria that drive quasispecies expansion and generates escape mutation. Replicative homeostasis explains both viral kinetics and the enigma of RNA quasispecies stability and provides a rational, mechanistic basis for all observed viral behaviours and host responses. More importantly, this paradigm has specific therapeutic implication and defines, precisely, new approaches to antiviral therapy. Replicative homeostasis may also modulate cellular gene expression.